Enhancing Novice Learners' Vocabulary Mastery Through Word Search Puzzle - Nurkamilah; Lista Dwi Noviyanti; Werdiningsih, Indah (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
Vocabulary is a stock of words or a collection of words owned by speakers or writers. According to Rahmah (2016), one of a language's most crucial components is vocabulary. It means that vocabulary is one of the language aspects which should be learnt. This research use Classroom Action Research. Classroom Action Research is the type of research used (CAR). According to Aqib, Z., and Chotibuddin (2018), the primary goal of CAR is to enhance the caliber of instruction in the classroom by resolving issues and developing pertinent and efficient corrective measures to enhance student learning outcomes and the caliber of the instructional process. The result is students’ vocabulary increased from 46,9% in the first cycle to 84,4% in the second cycle. In addition, student activity during learning also increased from 62.5% to 93.8%. Based on the findings and discussion, it can be concluded that novice learners’ vocabulary mastery has increased in the second cycle. The second cycle involves employing interactive learning in groups and three repetitions of the vocabulary pronunciation in the Word Search Puzzle. Test scores and student conduct during vocabulary learning both indicate changes in the rise. Thus, it can be said that Word Search Puzzle can enhance vocabulary mastery on novice learners through interactive learning and repetition of the material's pronunciation.